2010
DOI: 10.1097/brs.0b013e3181e9a156
|View full text |Cite
|
Sign up to set email alerts
|

ISSLS Prize Winner: A Study of Effects of In Vivo Mechanical Forces on Human Lumbar Discs With Scoliotic Disc as a Biological Model

Abstract: The study documents widespread changes in the EP and NP even in discs with minimal wedging. EP damage and alterations in diffusion were observed earlier than MRI changes and could indicate nutritional factors as the primary mechanism of degeneration induced by mechanical stress. Degeneration was more severe in caudal discs and those with truncal decompensation. Its implications on the timing and choice of surgery in scoliosis are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 73 publications
1
12
0
Order By: Relevance
“…Eur Spine J (2014) 23:1803-1814 1809 to abnormal environmental (load) stresses which may impact on their gene expression profiles [80,81]. Interestingly, results from microarray studies in our group confirm the presence of some of these proposed immature genes both in mature bovine and adult human NP.…”
Section: Cd239supporting
confidence: 74%
“…Eur Spine J (2014) 23:1803-1814 1809 to abnormal environmental (load) stresses which may impact on their gene expression profiles [80,81]. Interestingly, results from microarray studies in our group confirm the presence of some of these proposed immature genes both in mature bovine and adult human NP.…”
Section: Cd239supporting
confidence: 74%
“…Although the solute diffusion behaviors in human CEP were previously studied using the fluorescein-labeled markers and contrast agents (Rajasekaran, et al, 2004; Rajasekaran, et al, 2010; Roberts, et al, 1996), the diffusivity values of basic nutrient/metabolite (i.e., glucose/lactate) in healthy or degenerated human CEP are largely unknown. Glycolysis is believed to be the major energy metabolism pathway for disc cells in vivo by consuming glucose to generate adenosine triphosphate (ATP) and producing lactic acid as a waste product (Bibby, et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, the permeability coefficient of human CEP is found to be about 1/3 and 1/10 of that in human AF and cartilage (Maroudas et al, 1975). Compared with NP and AF tissue, previous studies also indicated that CEP has a unique 3D morphology, inhomogeneous biochemical composition, and regional dependent solute diffusion rate (Fields et al, 2014b; Rajasekaran et al, 2004; Rajasekaran et al, 2008; Rajasekaran et al, 2010; Roberts et al, 1989; Roberts et al, 1996). Therefore, we hypothesized that the biphasic viscoelastic properties of the CEP may also be regional dependent.…”
Section: Introductionmentioning
confidence: 99%